Impact Of Emergency Response Time On Survival Outcomes In Cardiac And Respiratory Arrest: A Systematic Review Of Time-Sensitive Resuscitation Benefits (The Review of Diabetic Studies, 2025)
Emergency response time is a pivotal determinant of survival in cardiac and respiratory arrest, where each minute of delay decreases the probability of successful resuscitation and favorable neurological outcomes. This systematic review evaluates evidence on response intervals and their influence on survival, return of spontaneous circulation (ROSC), and mortality in prehospital and in-hospital arrest scenarios. Following PRISMA 2020 guidelines and JBI/NOS quality appraisal frameworks, recent studies (2016–2025) indicate that survival declines steeply beyond the first 4 minutes without CPR, and that EMS arrival within ≤8 minutes yields the highest survival advantage in out-of-hospital cardiac arrest (OHCA), while delayed code-team activation in hospital settings (IHCA) similarly elevates mortality risk. The review underscores that optimized dispatch systems, rapid CPR initiation, and reduced no-flow duration markedly improve survival sensitivity to time. Findings confirm a strong inverse association between longer response times and survival outcomes, supporting strategic prioritization of response-time targets in emergency systems.